2003
DOI: 10.2527/2003.812395x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between scrotal circumference and female reproductive traits1

Abstract: ABSTRACT:Records for yearling scrotal circumference (SC; n = 7,580), age at puberty in heifers (AP; n = 5,292), age at first calving (AFC; n = 4,835), and pregnancy, calving, or weaning status following the first breeding season (PR1, CR1, or WR1, respectively; n = 7,003) from 12 Bos taurus breeds collected at the Meat Animal Research Center (USDA) between 1978 and 1991 were used to estimate genetic parameters. Age at puberty (AP) was defined as age in days at first detected ovulatory estrus. Pregnancy (calvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 34 publications
3
50
2
3
Order By: Relevance
“…However, Eler et al (2004) showed the importance of the inclusion of SC data to increase the accuracy of the prediction of genetic merit for HP, especially in the case of young bulls for which there is still no information regarding HP of the daughters. Martínez-Velá zquez et al (2003), in a study with 12 B. taurus breeds concluded that genetic response in the female reproductive traits through sire selection on yearling SC is not expected to be effective; and it is in agreement with Smith et al (1989), who reported non-significant relationships between age at puberty in heifers and SC of yearling males. The estimates of genetic correlation between SC-HP and SC-STAY obtained in this study show that there is no antagonism between these traits and permit us to infer that selection for SC leads to little or no improvement in reproductive traits of females and vice versa.…”
Section: Genetic Correlationssupporting
confidence: 78%
“…However, Eler et al (2004) showed the importance of the inclusion of SC data to increase the accuracy of the prediction of genetic merit for HP, especially in the case of young bulls for which there is still no information regarding HP of the daughters. Martínez-Velá zquez et al (2003), in a study with 12 B. taurus breeds concluded that genetic response in the female reproductive traits through sire selection on yearling SC is not expected to be effective; and it is in agreement with Smith et al (1989), who reported non-significant relationships between age at puberty in heifers and SC of yearling males. The estimates of genetic correlation between SC-HP and SC-STAY obtained in this study show that there is no antagonism between these traits and permit us to infer that selection for SC leads to little or no improvement in reproductive traits of females and vice versa.…”
Section: Genetic Correlationssupporting
confidence: 78%
“…These heritabilities are within the range, from 0.20 to 0.67, of other estimates for age at puberty (Arije and Wiltbank 1971;Smith et al 1976;Laster et al 1979). Reported heritability estimates for scrotal circumference range from 0.39 to 0.75 (Lunstra et al 1988;Martinez-Velazquez et al 2003;Corbet et al 2009). Our result for puberty in bulls (AGE26) was closer to the higher end of that range (h 2 = 0.78).…”
Section: Discussionmentioning
confidence: 52%
“…Thus, selection of early-maturing B. indicus heifers as well as nutritional protocols to advance puberty have received a great deal of interest from the scientific community (Vargas et al, 1998;Martinez-Velazquez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%